Perancangan Dan Penerapan Promotion Mix Pada Café Rumah Donut’s Tanjungpinang - Listia Nurjanah; Tiffani Tri Hanifa (ConCEPt - Conference on Community Engagement Project, 2021)
This program aims to implement the promotion mix strategy at Café Rumah Donut’s Tanjungpinang. In the implementing of the strategy in the form of advertising, sales promotion, and direct marketing. The approach of this program is using data collection techniques are observation and interview with the CEO. In accordance with the results of observations, it shows that Café Rumah Donut’s Tanjungpinang still implements a less active promotion system with the addition of a Word of Mouth (WOM). This makes marketing and promotional activities passive and only relies on regular customers or those who live in the area so that it is not widely known by the wider community. But after analyzing the problem and implementing the program, this cafe can develop and use a promotion system that has been designed by the executor. The promotion mix strategy directly plays a positive role in increasing sales turnover by 4.5% after this strategy is implemented.